An Overview and Criticality of High Availability and Disaster Recovery for SAP HANA - Lurduma Reddy Thirumala Reddy (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Setting up High Availability and Disaster Recovery for SAP HANA presents critical strategies for ensuring business continuity in enterprise environments. The implementation incorporates sophisticated architectural components for maintaining system operations through multi-layered redundancy and protection mechanisms. SAP HANA deployments leverage scale-out systems with coordinator and worker nodes, while system replication provides robust disaster recovery capabilities. Pacemaker cluster management enables automated failover and resource orchestration, with comprehensive testing frameworks ensuring system reliability. The architecture supports advanced features including active/active replication and tenant-level management, allowing organizations to achieve optimal resource utilization and granular control over high availability settings. These implementations demonstrate significant improvements in system performance, data consistency, and recovery capabilities, resulting in substantial reductions in downtime costs and data loss risks. The combination of strategic redundancy, proactive monitoring, and sophisticated replication mechanisms enables organizations to maintain continuous operations while meeting stringent service level agreements in mission-critical environments.